Effects of different corn straw amendments on humus composition and structural characteristics of humic acid in black soil. Issue 1 (2nd January 2020) - Zhang, Xiaowei; Dou, Sen; Ndzelu, Batande Sinovuyo; Guan, Xu Wen; Zhang, Bo Yan; Bai, Yue
ABSTRACT: Straw returning to the field has become a common way to utilize crop residues. This method does not only solve the problem of rational utilization of straw but also improves soil organic carbon (SOC) quality and quantity. So far, various methods of straw return exist, but the comparison of these methods has not been sufficiently studied, especially in the black soil of Northeast China. The purpose of this study is to evaluate the effects of different corn straw amendments applied under equal carbon (C) mass on soil humus composition and structural characteristics of humic acid (HA). The pot experiment was carried out by simulating corn straw return, which included four treatments: no corn straw applied (CK), corn straw (CS), humidified corn straw (HCS) and corn straw biochar (Bc). Soil HA was characterized by Fourier transform infrared spectroscopy (FTIR), elemental analyzer and thermogravimetric analysis (TG). The results showed that CS, HSC, and Bc treatments increased SOC content by 7.51%, 31.03%, and 33.65%, respectively, compared to CK. Bc treatment showed a greater degree of humification (79.16%) and increased the C content of HA by 10.87% and 7.37% compared with CS and HCS, respectively. The FTIR spectra and elemental results revealed that CS and HCS treatments increased the aliphaticity of the HA structure, while Bc increased the aromaticity of C in HA structure, rendering HA structure complicated. It can, therefore, be inferred that the application of biochar will improve humus compositions, SOC content and enhances the stability of HA structure.